Impact of linkage quality on inferences drawn from analyses using imperfectly matched data with high rates of linkage errors. (2018) - Rentsch, Christopher; Reniers, Georges; Harron, Katie; Machemba, Richard; Mtenga, Baltazar; Michael, Denna; Kabudula, Chodziwadziwa; Natalis, Redempta; Urassa, Mark; Todd, Jim; Zaba, Basia
No abstract available